Escolarização de jovens e adultos - Sérgio Haddad; Maria Clara Di Pierro (Associacao Nacional de Pós-Graduação e Pesquisa em Educação, 2000)
The article covers the systematic and organized processes of general education offered to youth and adults, carried out in Brazil, in the light of public policies. It offers an overview of this theme throughout the five hundred years of Brazilian history and dedicates special attention to the last half of the 20th century in which pedagogical tenets and school education policies for youth and adults take on specific features. It analyses the political meaning that the military dictatorship imputed to adult literacy programs and post literacy education in the 70s, the several designs taken on by youth and adult school education public policies throughout the process of redemocratization in the 80s, as well as the marginal position that has been given to this type of education in the 90s. The essay indicates as a challenge the redefinition of public sector and society rules in democratizing opportunities for literacy, basic schooling and continued education in order to respond to the growing formative needs of young and adult people in contemporary Brazil.